1993
DOI: 10.1007/bf00662401
|View full text |Cite
|
Sign up to set email alerts
|

Toremifene and tamoxifen in advanced breast cancer - a double-blind cross-over trial

Abstract: Toremifene (TOR) is a triphenylethylene derivative related to tamoxifen (TAM). TOR has antitumor activity, not dependent on estrogen receptors, and responses with TOR have been observed in patients with progressive disease during TAM-treatment. To elucidate possible cross-resistance between these two antiestrogens, we compared their anti-tumor activity in a randomized, double-blind, cross-over study. 66 postmenopausal women with advanced estrogen receptor positive or unknown breast cancer and a median age of 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…Tamoxifen is a triphenylethylene derivative commonly used in the treatment of breast cancer (Furr and Jordan 1984;Hayes et al 1995;Knapp et al 1994;Nayfield et al 1991;Stenbygaard et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Tamoxifen is a triphenylethylene derivative commonly used in the treatment of breast cancer (Furr and Jordan 1984;Hayes et al 1995;Knapp et al 1994;Nayfield et al 1991;Stenbygaard et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Toremifene (TOR) is a selective estrogen receptor modulator (SERM). It has been reported that the efficacy of treatment with this agent in cases of postmenopausal breast cancer is similar to that of TAM [3,4]. The usual dose of TOR is 40 mg given orally once a day; however, high-dose TOR (120 mg a day; TOR120) has been approved for use in Japan.…”
Section: Introductionmentioning
confidence: 98%
“…High-dose TOR was reported to compete with estrogen at the site of the ER, to suppress insulin-like growth factor-I-dependent growth [19], and to have non-ER-dependent anti-tumor effects such as suppression of angiogenesis [20,21]. In addition, the agent is effective in TAM-resistant breast cancer and can be used as a secondary endocrine therapy [3,22].…”
Section: Introductionmentioning
confidence: 99%
“…Toremifene has a high affinity for the estrogen receptor in breast cancer, is active against the breast cancer, and has an antitumor activity. Stenbygaard et al 10 and Pagani et al 9 affirmed that no significant difference in response rate, duration, survival, and toxicity in the treatment of patients with breast cancer has been shown for toremifene and tamoxifen. In preclinical studies, toremifene has been shown to cause less DNA-adduct formation and to have less estrogenic activity in the endometrium.…”
Section: Discussionmentioning
confidence: 99%
“…Although tamoxifen is still the anti-estrogen of choice in the treatment of breast cancer patients, many clinicians consider toremifene to be a valid and safe alternative to tamoxifen in endocrine-responsive breast cancer, for similar anti-tumor effects and the possibility of a lower incidence of treatment-related endometrial malignancies. 6,[8][9][10] Toremifene is a triphenylethlene derivative related to tamoxifen. Toremifene has a high affinity for the estrogen receptor in breast cancer, is active against the breast cancer, and has an antitumor activity.…”
Section: Discussionmentioning
confidence: 99%